3D navigation system based on synthetic texturing - Alizadehashrafi, Behnam (Penerbit UTM, 2008)
Navigation system is the order of the day to pilot people to their destination. This paper focuses on the uses of mobile devices such as PDA’s and smart phones without additional hardware to direct pedestrians based on synthetic texturing along with 3D modeling. Each façade is reconstructed by means of arraying small sized textures in respect to their geometries in different layers. In the process of texture generation cropping, rectifying, removing disturbing objects and exposure setting should be done in advance. Unlimited number of layers with different priorities and their horizontal and vertical pulse functions and texture files can be utilize d for creating a simple and square looking façade. Each 3D model is created by mapping the synthetic textures on the 3D geometries of each building’s 3D model.